Fluorescence switching of sanguinarine in micellar environments. Issue 32 (24th July 2015) - Satpathi, Sagar; Gavvala, Krishna; Hazra, Partha
Abstract : Conversion from iminium to alkanolamine form of Sanguinarine, a key member of benzylisoquinoline alkaloid family, is monitored in micellar environments by fluorescence switch. Abstract : Sanguinarine (SANG), a key member of the benzylisoquinoline alkaloid family, is well-known for its various therapeutic applications such as antimicrobial, antitumor, anticancer, antifungal and anti-inflammatory etc. Depending on the medium pH, SANG exists in the iminium or alkanolamine form, which emits at 580 nm and 420 nm, respectively. Nucleophilic attack on the C6 carbon atom converts the iminium form to the alkanolamine form of SANG, and these two forms are equally important for the medicinal activities of SANG. To improve its potency as a drug, it is essential to get a physical insight into this conversion process. In this study, we have deployed steady sate and time-resolved spectroscopic techniques to probe this conversion process inside different micellar environments. We have observed that the conversion from the iminium to alkanolamine form takes place in neutral OBG (octyl-β-d -glucopyranoside) and positively charged CTAB micelles, whereas the iminium form exclusively exists in negatively charged SDS micelles. This conversion from the iminium to alkanolamine form in the case of OBG and CTAB micelles may be attributed to the reduced p K a of this conversion process owing to the enhanced hydrophobicity experienced by the iminium form in between the surfactant head groups. On the other hand, the electrostatic attraction between positively charged iminium and negatively charged surfactant head groups stabilizes the iminium form in the stern layer of the SDS micelle. We believe that our observations are useful for selective transportation of any particular form of the drug into the active site. Moreover, loading of any particular form of drug can be easily monitored with the help of fluorescence color switch from orange (iminium) to violet (alkanolamine) without pursuing any sophisticated or complex technique.